Modeling road-tyre noise - Martins, Mário M. Abreu (2008)
The growing awareness by the broader public of the consequences to health and wellbeing due to road noise has led to a growing number of legal requirements being produced to deal with this matter, both in the design of new or assessment of existing infrastructure. In this article the purpose is to make an up-to-date review of existing studies being carried out to deliver models for predicting noise produced from tyre-road contact, taking account of different methodological approaches which, particularly in Europe thanks to EU sponsored projects, intend to deliver practical solutions regarding different structural solutions and the use of new materials. The main goal of this work is to provide some insight about which approach is better suited to be used in a practical noise prediction model for Portuguese roads, to take into account its specific environmental characteristics and physical features of construction materials.